Downward but stable trend in the abundance of arribada olive ridley sea turtles (Lepidochelys olivccea) at Nancite Beach, Costa Rica (1971-2007) - Fonseca, Luis (2009)
– Although the olive ridley sea turtle (Lepidochelys olivacea) is the most abundant sea turtle in the world, the species has exhibited a significant decrease in the size of arribadas at Nancite Beach, Costa Rica, since its discovery in 1970. In the present study, we compiled data on number of nesting females per arribada from previous authors for the period 1971–1997 and collected new data using a total count methodology and a strip transect method for the arribadas during 1999–2007. We used generalized additive models to assess the trend of arribada size for the period 1971–2007. Our data indicate a significant reduction of 42%, 84%, and 90% in the number of nesting females per arribada in the periods 1971–1984, 1971–1992, and 1971–2007, respectively. Although we could not determine the specific reasons for this attrition we speculate that this decline may be driven by embryo-associated mortality due to a poor nest microenvironment in this beach. Our data confirm that the Nancite arribada population has undergone a significant decrease over the past 36 years but that the population currently appears to be at a stable low point. In addition, our data show that hatchling production may be increasing at this beach, which suggests the possibility that this population may recover over a few decades. The significant attrition observed in this study underscores the ephemeral nature of arribada populations in general and the need for the continued monitoring of the Nancite population